Happiness and economic growth: The evidence - Richard A. Easterlin (Institute for the Study of Labor (IZA), 2013)
Long term trends in happiness and income are not related; short term fluctuations in happiness and income are positively associated. Evidence for this is found in time series data for developed countries, transition countries, and less developed countries, whether analyzed separately or pooled. Skeptics, who claim that the long term time series trend relationship is positive, are mistaking the short term association for the long term one, or are misguided by a statistical artifact. Some analysts assert that in less developed countries happiness and economic growth are positively related up to some point, beyond which the association tends to become nil, but time series data do not support this view. The most striking contradiction is China where, despite a fourfold multiplication in two decades in real GDP per capita from a low initial level, life satisfaction has not improved.
Keywords: I31; D60; O10; O5; 330; happiness; life satisfaction; subjective well-being; income; long term; short term; Easterlin paradox; developed countries; transition countries; less developed countries; China